The Experience of Selling Second-Hand Wearable (Preloved) Clothing Online: Digital Marketing Strategies and Their Implications for Sustainability - Indra Sudrajat (Penerbit Hellow Pustaka, 2026)
Digital transformation has reshaped consumption and distribution patterns in the fashion industry, including the increasing practice of selling second-hand wearable clothing (preloved) online. This study aims to analyze the experience of selling preloved clothing through digital platforms, identify the determinants of business success, and examine its contribution to sustainability principles. A qualitative descriptive approach was employed using participatory observation and documentation of digital sales activities. The findings reveal that the success of a preloved business is determined by product quality, visual-based digital marketing strategies, consumer interaction, and trust-building. Beyond generating economic benefits, this business model supports the concept of sustainable fashion by extending product life cycles and reducing textile waste. The study reinforces recent national research indicating that thrifting and preloved trends represent a shift in consumer behavior toward a circular economy.